Molecular recognition of anions by synthetic receptors. - Beer, P; Schmitt, P (1997)
Over the past year, several significant developments have been made in the field of anion binding. The fundamental principles of molecular recognition are increasingly being better understood, and of particular interest are reports of several synthetic anion receptors able to perform their task in complex natural media. Additionally, macroscopic devices such as anion specific electrodes and membranes based on a molecular recognition approach are now being made.